Flavins Act as a Critical Liaison Between Metabolic Homeostasis and Oxidative Stress in the Retina - Sinha, Tirthankar; Naash, Muna I.; Al-Ubaidi, Muayyad R. (Frontiers in Cell and Developmental Biology, 2020)
Derivatives of the vitamin riboflavin, FAD and FMN, are essential cofactors in a multitude of bio-energetic reactions, indispensable for lipid metabolism and also requisite in mitigating oxidative stress. Given that a balance between all these processes contribute to maintenance of retinal homeostasis, effective regulation of riboflavin levels in the retina is paramount. However, various genetic and dietary factors have brought to fore pathological conditions which co-occur with suboptimal level of flavins in the retina. Our focus in this review is to comprehensively summarize all the possible metabolic and oxidative reactions which have been implicated in various retinal pathologies and to highlight the contribution flavins may have played in these. Recent research has found a sensitive method of measuring flavins in both diseased and healthy retina, presence of a novel flavin binding protein exclusively expressed in the retina and the presence of flavin specific transporters in both the inner and outer blood-retina barriers. In light of these exciting findings, it is even more imperative to shift our focus on how the retina regulates its flavin homeostasis and what happens when this is disrupted.